Epidemic Deioliation of Poplars and its Control in Tarai Central Forest Division, Uttar Pradesh - Singh, Pratap; Rawat, D. S.; Misra, R. M.; Fasih, Massrat; Prasad, G.; Tyagi, B. D. S. (Indian Forester, 1983)
no abstract